Case Study : D’Niz Patin Oriee / Muhammad Zuhair Zakaria - Zakaria, Muhammad Zuhair (2020)
The name of the restaurant is D’NIZ PATIN ORIEE which is the combining name the owner and his wife which is D from Affendi and NIZ from Niza. Some technology used by the restaurant was debit pay, ordering by using tablet and security camera to monitor the condition at the restaurant. The owner has the target to expand his business branch around Malaysia. The strength of the restaurants is that they provided high quality of food before they serve to the customer. The restaurant also set the affordable price to people buy their foods. The biggest opportunity is the restaurant give all their commitment to the customers needs and serve the better service to maintaining their relationship within customers